Analysis of Factors Affecting Student Entrepreneurial Interest in Private Catholic Universities in Samarinda City - Anggal, Nikolaus; Samdirgawijaya, Wilfridus; Lio, Zakeus Daeng; Silpanus, Silpanus (Budapest International Research and Critics University, 2021)
Entrepreneurship education has received considerable critical attention in the last decade. The basic reason is that entrepreneurship can reduce social and economic problems such as unemployment and poverty. Given the importance of entrepreneurship, both developed and developing countries have responded by programming to increase entrepreneurship in their countries, including Indonesia. This qualitative study aims to determine the factors that influence students' interest in entrepreneurship. The population of this study was 114 students of the Catholic Religious Education study program who had taken entrepreneurship courses and had participated in entrepreneurship training and workshops on campus. The results of this study indicate that personality factors have a positive effect on students' interest in entrepreneurship with an rx1y value of 0.755; r2x1y is 0.570 with the regression equation is Y-0.595X1 + 11.304. Family factors also have a positive effect on interest in entrepreneurship with an rx2y value of 0.515; r 2 x2y is 0.265 with the regression equation is Y = 0.694X2 + 17.867. Then, the peer factor has a positive effect on students' interest in entrepreneurship, the value of rx3y is 0.453; r2x3y is 0.205 with the regression equation is Y = 0.537X3 + 21.916. Based on these results, the recommendation that can be given is that there is a need for improvement for the campus in providing understanding and entrepreneurship training in order to increase the interest and ability of students in entrepreneurship, so that graduating from college has enough confidence, quasi-knowledge, and abilities obtained for further practiced by entrepreneurship or creating jobs.